تسكين آلام المخاض باستخدام تقنية القثطرة فوق الجافية - سلامة, عبد الهادي; يوسف, أحمد; وليد, مالك (Latakia University Journal -Medical Sciences Series, 2019)
أجريت الدراسة في مشفى الأسد الجامعي في اللاذقية في قسم التخدير و الإنعاش بالتعاون مع قسم التوليد و أمراض النساء خلال العام 2005 – 2004 . وتضمنت 50 ماخضاً خروساً. وكانت نتائج الدراسة على النحو التالي: النسبة الأعلى للمواخض الخروسات في الدراسة ضمن الفئة العمرية(21-25) بنسبة 40%. كانت النسبة العظمى للمواخض الخروسات اللواتي أجري لهن تخدير فوق الجافية باتساع عنق رحم 4-6 سم (70%). أعلى نسبة للمواخض الخروسات حسب العمر الحملي بين 38-40 أسبوعاً حملياً ( 76% ). انتهت النسبة العظمى من الولادات بالطريق الطبيعي ( المهبلي ) و بنسبة 94%. كانت النسبة الأعلى لدرجة الأ لم IV حسب المقياس الشفهي البسيط قبل تطبيق التخدير فوق الجافية (70%) وبعد تطبيق التخدير أصبحت الدرجة I هي الغالبة(90%). ضمت الدرجة V للألم حسب المقياس السلوكي أعلى نسبة من المواخض(76%) بينما شملت الدرجةI النسبة الأعلى بعد التخدير (88%). كان أبغار النسبة العظمى من الولدان (7-10) في الدقيقة الأولى(82%) وفي الدقيقة الخامسة(98%). وتحركت معظم الولودات خلال الساعات الأربع الأولى بعد الولادة(88%). الاختلاطات: حدث: احتباس بولي لدى ماخض واحدة فقط و بنسبة 2%. غثيان لدى ماخض واحدة فقط و بنسبة 2%. صداع صدغي لدى ماخض واحدة فقط و بنسبة 2% و قد زال هذا الألم في اليوم الثالث بعد الولادة و دون تناول أية مسكنات. ألم ظهري بنسبة 6%. التبدل في قيمة الضغط الشرياني الوسطي تمثل بانخفاض ذي أهمية إحصائية بعد 5 دقائق من حقن المادة المسكنة أمابالنسبة للنبض القلبي فكان مع الدقيقة 60. أبدت معظم المريضات ارتياحاً وتقبلا للتخدير فوق الجافية. This study was carried out in The Department of Anesthesia and Reanimation in Collaboration with The Department of Obstetrics and Gynecology at ALASSAD University Hospital in Lattakia during the year 2004 – 2005, and included 50 nullipara parturients. The results were: The highest percentage of nullipara parturients was in the group of patients between 21-25 years old (40%). The highest percentage of nullipara parturients who were epiduralized at 4-6 cm of cervical distension was (70%). The highest percentage of nullipara parturient was between 38-40 weeks of pregnancy (76%). The highest percentage of deliveries was normal (Vaginal) (94%). The highest percentage of pain in the simple oral evaluation was at the fourth IV degree before epidural (70%) and after epidural it became in the first degree I (90%). The highest percentage of pain in the Behavioral evaluation was at the fifth V degree before epidural (76%) and after epidural it became in the first degree I (88%). Neonates Apgar score was 7-10 in the first minute 82% and in the fifth minute 98%. Most of patients were able to move during the four hours after delivery (88%). Complications: Urinary retention occurred in one patient (2%). Nausea occurred in one patient (2%). Temporal headache occurred in one patient (2%), and disintegrated in the third day after delivery without analgesics. Back pain (6%). The hypotension was important statistically after 5 minutes of analgesic injection. The change in the heart rate was important statistically after 60 minutes of analgesic injection. Most of patients were satisfied with labor pain analgesia by epidural technique.